Informal Insurance Arrangements in Ethiopia: A Literature Review - Beshir, Howlet A.; Alhabshi, Syed M.; Zakariyah, Habeebullah (Asian Scholars Network, 2021)
Various researches on informal financial sector presented its potential to achieve financial inclusion among low-income households. Apart from social networking, the informal financial sector will likely continue to be important in developing countries as well as among immigrants in developed countries in terms of financial access and support. Among the informal financial mechanisms, informal insurance arrangements are popular in developing countries whose beneficiaries include mainly low-income households. This article presents the general overview of informal insurance arrangements, mainly the Ethiopian iddir in Ethiopian communities and to explore whether these arrangements can complement with formal insurance services.